Development of Mathematical Models to Control the Underground Leaching Process - Ismanova Klara Dulanboevna (Global Scientific Publishing, 2023)
The article analyzes the physical and chemical foundations of the in-situ leaching process, data processing using approximate analytical solutions to predict the required parameters and verify the reliability of the developed process control model, and conduct a system analysis of the in-situ leaching process as an object of study
Keywords: Underground teaching; the useful component; the concentration